Blt1 and Mid1 Provide Overlapping Membrane Anchors To Position the Division Plane in Fission Yeast - Guzman-Vendrell, Mercè (American Society for Microbiology, 2013)
Spatial control of cytokinesis is essential for proper cell division. The molecular mechanisms that anchor the dynamic assembly and constriction of the cytokinetic ring at the plasma membrane remain unclear. In the fission yeast Schizosaccharomyces pombe, the cytokinetic ring is assembled in the cell middle from cortical node precursors that are positioned by the anillin-like protein Mid1. During mitotic entry, cortical nodes mature and then compact into a contractile ring positioned in the cell middle. The molecular link between Mid1 and medial cortical nodes remains poorly defined. Here we show that Blt1, a previously enigmatic cortical node protein, promotes the robust association of Mid1 with cortical nodes. Blt1 interacts with Mid1 through the RhoGEF Gef2 to stabilize nodes at the cell cortex during the early stages of contractile ring assembly. The Blt1 N terminus is required for localization and function, while the Blt1 C terminus promotes cortical localization by interacting with phospholipids. In cells lacking membrane binding by both Mid1 and Blt1, nodes detach from the cell cortex and generate aberrant cytokinetic rings. We conclude that Blt1 acts as a scaffolding protein for precursors of the cytokinetic ring and that Blt1 and Mid1 provide overlapping membrane anchors for proper division plane positioning.